Multifractal analysis and optical properties of nanostructured silicon layers - Jurečka, Stanislav; Matsumoto, Taketoshi; Imamura, Kentaro; Kobayashi, Hikaru (Applied surface science, 2017)
[Display omitted] •SSCT etching of silicon.•Anizotropic etching.•Multifractal detrended fluctuation analysis of SEM and AFM images.•Fourier analysis of SEM and AFM images.•Particle size enhancement of Raman scattering. For the optimization of the light trapping in semiconductor devices, especially in the solar cells, microtextured structures are commonly used. Structures with ultralow spectral reflectance were formed on flat and pyramidally textured single crystalline silicon wafers by using of the surface structure chemical transfer method (SSCT). This method is based on effective etching of treated surface in HF solution in contact with a Pt mesh. The structure of the SSCT layer is determined by the etching conditions and influences substantially its optical properties. We studied microstructural properties of the SSCT layers by the SEM and AFM methods and we analyzed obtained morphological information by the multifractal (MF) and Fourier methods. The properties of etched surface layers determine the spectral reflectance and Raman scattering. Exponential fall of the spectral reflectance is caused by the gradient of layer density and enhancement of Raman scattering is related to forming of small particle size fraction during the SSCT etching. Results of MF and Fourier analysis are used in interpretation of the optical properties of formed microtextured structures.